Pengeringan Passive Irisan Umbi Uwi (Dioscorea alata L.) - Iqbal; Irwan T; Junaedi Muhidong (Jurnal Agritechno, 2020)
ABSTRACT Passive drying is a drying mechanism that utilizes sunlight in a drying chamber with natural air flow mechanism. The tool used is direct passive solar box dryer. Direct type passive drying is a drying mechanism in a drying chamber with an air flow mechanism where direct sunlight enters the drying chamber. This study was intended to determine the pattern of decreasing water content and moisture ratio of yum (Dioscorea alata L.) and the appropriate drying model. Passive drying of yum tuber slices is done in two stages. The first drying data is used to determine the most suitable drying model (biggest R2). While the second drying data is used to validate the accuracy of the model predictions obtained. The drying process is carried out by placing the sample at the top, middle, and bottom of the drying chamber. The samples used are two types of yum namely white yum and purple yum with a size of 3x3x1 cm. The models evaluated for compatibility are Newton, Henderson & Pabis, and Page. The results of the analysis show that the Page model with the equation MR = exp (-ktn) is the most suitable model to describe the pattern of decreasing water content and moisture ratio of yum. The values ​​of the Page equation constants are obtained as follows: k = 0.187249, n = 1.17272 and R2 = 0.999403. Keywords: Yum, Drying, Drying Model, Water Content